Detection of cutaneous malignant melanoma using RNA sampled by tape strips: A study protocol - Ida M. Heerfordt; Jeppe D. Andersen; Peter A. Philipsen; Linnea Langhans; Torben Tvedebrink; Grethe Schmidt; Thomas Poulsen; Catharina M. Lerche; Niels Morling; Hans Christian Wulf (PLoS ONE, 2022)
Background Cutaneous malignant melanoma (CMM) is curable if detected in its early stages. However, the clinical recognition of CMM is challenging. An American research group has shown promising results in detecting CMM based on RNA profiles sampled from suspicious lesions with tape strips. We aim to further develop this technique and validate if RNA profiles sampled with tape strips can detect CMM. Methods This prospective cohort study will include approximately 200 lesions clinically suspected of CMM requiring surgical removal. Tape stripping of the lesions will be performed just before surgical excision. Subsequently, RNA on the tape strips is analyzed using quantitative real-time polymerase chain reaction with TaqMan technology. The results are combined into a binary outcome where positive indicates CMM and negative indicates no CMM. The histopathological diagnosis of the lesions will be used as the gold standard. The main outcome is the results of the RNA test and the histopathological diagnosis, which, combined, provide the sensitivity and specificity of the test. Discussion The accuracy of the clinical examination in CMM diagnostics is limited. This clinical trial will explore the ability to use RNA analysis to improve the management of suspicious lesions by enhancing early diagnostic accuracy. Hopefully, it can reduce the number of benign lesions being surgically removed to rule out CMM and decrease patient morbidity. Trial registration The project was approved by The Committee on Health Research Ethics of the Capital Region of Denmark (H-15010559) and registered at the Danish Data Protection Agency (BFH-2015-065).